A Study On The Effect Of Attractiveness, Pragmatic, And Hedonic Quality On The User Experience Of A Dark Mode Mobile Reading Application On Young User In China - Yang, Aiyi (2024)
The concept of dark mode originated in the early development stages of computer displays. With the advancement of screen technology and the proliferation of mobile devices, dark mode regained attention in the early 21st century. Notably, in 2019, iOS 13 and Android 10 introduced system-wide dark modes, making this feature prevalent on mainstream mobile devices. Although dark mode has become widely adopted commercially, academic research on dark mode, particularly regarding user experience, remains limited. This study investigates the dimensions of Attractiveness, Pragmatic Quality, and Hedonic Quality in the dark mode user experience of mobile reading applications among young users in China. Using a mixed research methodology, data were collected based on a systematic framework and the UEQ theory. A quantitative questionnaire survey measured the user experience across three UEQ categories (six attributes), and qualitative interviews were used for triangulation of the results. Findings indicate that Attractiveness received the highest feedback, Hedonic Quality the lowest, and Pragmatic Quality results were moderately high. Notably, there were subjective differences between the questionnaire and interview results for Hedonic Quality. This study provides valuable insights for designers and developers to improve dark mode user experiences, offering reference data and suggestions to enhance design effectiveness. It fills a research gap regarding young users' experiences with mobile reading applications in dark mode and serves as a reference for future research.